Mango enriched with sucrose and isomaltulose (Palatinose®) by osmotic dehydration: Effect of temperature and solute concentration through the application of multilevel statistical models - do Carmo, Juliana Rodrigues; Corrêa, Jefferson Luiz Gomes; Resende, Mariana; Cirillo, Marcelo Ângelo; Corona-Jiménez, Edith; Telis-Romero, Javier [UNESP] (Wiley, 2022)
Osmotic dehydration (OD) is useful for the enrichment of mangos with interesting solutes. Isomaltulose has healthier properties than sucrose and its use is still scarce in OD processes. The OD of mangos with isomaltulose and sucrose was evaluated, and the effect of solute concentrations (25%, 30%, 35%) and temperatures (25, 35, 45°C) was estimated by multilevel statistical analysis in order to find the best conditions for a greater water loss (WL) and solid gain (SG). In sucrose OD, the highest concentration (35%) had the greatest effect than the temperature for WL and SG. For isomaltulose OD, the concentration provided greater WL and SG, but the effect of temperature was slightly more expressive for SG than WL. The maximum working conditions (35% of isomaltulose or sucrose and 45°C) promoted greater WL and SG for both carbohydrates, and with the OD it was possible to enrich mango with isomaltulose by taking advantage of the osmotic gradient, getting an osmodehydrated product with low glycemic and isulinemic indexes. Novelty impact statement: Through the osmotic dehydration, it is possible to enrich mango samples with isomaltulose due to its healthy attributes. Instead, a traditional statistical analysis, the multilevel statistical modeling was applied, which was suitable for evidence that the highest solute concentration and temperature conditions promoted the greatest water loss and solid gain, favoring the enrichment process.